Vehicle tracker system design based on GSM and GPS interface using arduino as platform - Narcisa T. Morallo (Institute of Advanced Engineering and Science, 2021)
Global positioning system (GPS) tracker is an innovative technology that is able to track the position of vehicle using global satellite system. In this paper, vehicle tracker system design that is derived from global positioning system and global system for mobile communication (GSM) interface with the use of Arduino Uno board as platform is proposed and presented. Technology in Arduino, GSM, and GPS is studied.GPS module receives the coordinates from the satellite. The GPS coordinates are sent to users in the form of SMS through SIM900A GSM module. By using Google Maps, the exact location of the vehicle can be located. Arduino microcontroller is the gateway to all GPS and GSM hardware and software communication in the system. The design represents that GSM and GPS interface with the use of Arduino Uno board as platform can really make vehicle tracking more efficient and convenient since it can work in any weather conditions and provide real-time location of objects. Automatic display of the coordinate’s geographical location in a map should be integrated in future design.